Qualitative Assessment of Economic Mobility and Labor Markets in Turkey : A Gender Perspective - World Bank (World Bank, Washington, DC, 2016)
Turkey has recently experienced significant population growth, gross domestic product (GDP) growth, and modernization. The economic structure in Turkey has been changing rapidly due to privatization and global growth. This report examines men and women’s perception of factors that are perceived to shape their economic mobility, access to labor markets, and entrepreneurship opportunities across multiple community contexts in Turkey. Relevant literature and data was first reviewed to inform the hypotheses and survey analysis. Based on the review of the relevant literature, it is expected that in terms of the middle class overall, men and women will report a lack of education and appropriate skills as barriers to both employment and entrepreneurship opportunities. Economic mobility, supported by a thriving and open labor market, targeted policies, and an enabling environment for entrepreneurs, is a key requisite for improving living standards, wellbeing, and the reduction of unemployment and poverty. The first section gives introduction. The second section discusses research approach and defines hypotheses, which are later addressed using the qualitative survey information. The third section presents the results and findings derived from the analyzed information and data. The fourth section summarizes the main conclusions and provides recommendations for policy makers. Finally, the annex covers an overview of the country context with special emphasis on the labor market in Turkey, women’s roles in society and economy, and labor policy reforms in Turkey.